Nexus between Blue Economy, Renewable Energy and Environmental Sustainability in the MENA Region: Evidence from Panel Threshold Regression - Elsherif, Marwa (International Journal of Energy Economics and Policy, 2024)
This paper attempts to investigate the relationship between blue economic activities, renewable energy and the ecological footprint in the MENA region from 2000 to 2022. The study utilizes the STRIPAT model, thus, the methodology involves multiple econometric techniques such as cointegration tests, quantile via moment, threshold regression and panel Granger causality test. Estimates confirm a significant negative impact of renewable energy consumption and innovations on the ecological footprint, while the effect of the total fisheries production, GDP per capita as well as urban population growth on the ecological footprint is positive and consistent across the study period. The findings reveal the role of extensive economic activities, extensive seas and oceans activities and urbanization as major drivers of environmental damages and the subsequent increase in ecological footprints. Therefore, by promoting sustainable practices and renewable energy utilization, MENA countries can effectively mitigate their ecological footprints and contribute to global climate change mitigation efforts. The study also emphasizes on the significance of sustainable practices and the need for comprehensive policy measures to mitigate the ecological footprint and promote a more environmentally conscious society.